Acute Necrotizing Encephalopathy Associated with Influenza A. (2nd January 2020) - Bailey, Heather E.
ABSTRACT: A severe and unusual complication found in children with influenza is an acute necrotizing encephalopathy. A 20-month-old female with no significant past medical history was admitted to our facility, presenting with a 4-day history of worsening fever, upper respiratory symptoms, new-onset altered mental status and episodes of extensor posturing. The initial concern was a dystonic reaction secondary to promethazine following a recent diagnosis of influenza A virus. A head computed tomography scan indicated concern for widespread edema, and the video EEG revealed focal slowing in the frontocentral regions with no epileptiform activity during episodes of extensor posturing. The first magnetic resonance imaging results were consistent with acute hemorrhagic encephalitis or severe anoxic brain injury for which there is a broad differential. A second MRI five days later found new areas of restricted diffusion that were consistent with acute necrotizing encephalitis.